A brief self‐compassion intervention for adolescents with type 1 diabetes and disordered eating: a feasibility study. Issue 11 (11th July 2020) - Boggiss, A. L.; Consedine, N. S.; Schache, K. R.; Jefferies, C.; Bluth, K.; Hofman, P. L.; Serlachius, A. S.
Abstract: Aim: To examine the feasibility and acceptability of a brief self‐compassion intervention for adolescents with type 1 diabetes and disordered eating behaviour. Methods: Twenty‐seven adolescents with type 1 diabetes were recruited and randomized to receive the brief (two 2.5‐h sessions) self‐compassion intervention, either in the intervention group ( n =11) or in a waitlist control group ( n =8). The intervention was adapted from the standardized eight‐session 'Making Friends with Yourself' programme, and sessions were delivered 1 week apart. Acceptability was assessed through qualitative questionnaires and feasibility was assessed based on session attendance and recruitment metrics. Possible changes to disordered eating behaviour, self‐care behaviours, diabetes‐related distress, self‐compassion, stress and glycaemic control were also assessed. Results: Nineteen participants completed the study, and they reported an increased sense of common humanity (acknowledging that we are not alone), mindfulness, and coping resources. In terms of feasibility, recruitment took longer than expected (8 months) and not all participants were able to attend both sessions (nine could only attend one of the two sessions). Conclusions: While self‐compassion is a strong conceptual fit for the issues of type 1 diabetes and disordered eating behaviour in adolescence, and the intervention content appears acceptable, feasibility issues were such that brief self‐compassion programmes will probably need to be adapted into digital interventions for future research. (Trial registration number: ANZCTR 12619000541101). What's new?: The study is the first to perform a preliminary evaluation of a clinically usable, brief self‐compassion intervention for adolescents with type 1 diabetes and disordered eating behaviour. Self‐compassion appears acceptable and of good conceptual fit for the difficult emotions and stressors faced by this population. Qualitative data suggest the brief self‐compassion intervention may be effective by increasing coping, perceptions of common (shared) humanity, and mindfulness. Despite the programme's acceptability, delivering the brief self‐compassion programme face to face was of limited feasibility, therefore, future research will probably need to explore digital adaptions.